Hemodynamic Monitoring During Heated Intraoperative Intraperitoneal Chemotherapy Using the FloTrac/Vigileo System - Mavroudis, Christos (Int Surg, 2015)
Cytoreductive surgery with HIPEC has provided a chance for long-term survival in selected patients. However, perioperative management remains a challenge for the anesthesiology team. The aim of this study was to evaluate the changes in hemodynamic parameters during hyperthermic intraperitoneal chemotherapy (HIPEC) using the FloTrac/Vigileo system. Forty-one consecutive patients undergoing cytoreductive surgery and HIPEC were enrolled. Heart rate (HR), esophageal temperature, and cardiac output (CO) steadily increased until the end of HIPEC. In the first half of HIPEC, systolic blood pressure (SBP) and central venous pressure (CVP) increased whereas systemic vascular resistance (SVR) decreased; SVR stabilized in the second half. Diastolic blood pressure (DBP), mean arterial pressure (MAP), and stroke volume (SV) showed no significant variation. Male gender was related to increased CVP, CO, and SV, and decreased SVR; age >55 years was related to increased SBP, and peritoneal cancer index (PCI) was correlated with HR, DBP, and SV. PCI >14 was associated with increased HR and decreased DBP and MAP. American Society of Anesthesiologists score >1 was related to decreased CO and SV. Patients undergoing HIPEC develop a hyperdynamic circulatory state because of the increased temperature, characterized by a steady decrease in SVR and continuous increase in HR and CO. FloTrac/Vigileo system may provide an easy-to-handle, noninvasive monitoring tool.